THE INFLUENCE OF HUMAN RESOURCE QUALITY ON PERFORMANCE CREW SHIP AT BOURBON OFFSHORE ASIA PTE.,LTD - PURBA, JULYANA; Arifian, Naf'an (Jurnal Cakrawala Bahari, 2025)
This study aims to analyze the influence of Human Resource (HR) quality on crew performance at Bourbon Offshore Asia Pte., Ltd. The main focus of the research is how HR quality affects the operational effectiveness of ships, which directly impacts safety and work efficiency in the maritime environment. This study employs a quantitative method using a questionnaire instrument that has been tested for validity and reliability. The data is analyzed using linear regression to determine the relationship between HR quality and crew performance. The results indicate that the majority of crew members have 0–4 years of work experience, highlighting the need for more effective training strategies to enhance their competencies. In terms of job distribution, 53.75% of the crew consists of deckhands (ABK), who play a crucial role in daily ship operations. The regression test results show a positive and significant effect between HR quality and crew performance, with a correlation value of 0.926. The coefficient of determination (R² = 0.857) indicates that 85.7% of crew performance variation is explained by HR quality, while 14.3% is influenced by other factors. Key factors improving crew performance include individual competence, work productivity, and compliance with safety standards. However, aspects such as work initiative and task completion require further attention.